The Influence of Corporate Social Responsibility on Firm Value in Banking Companies Listed on the Indonesia Stock Exchange: Reputation as a Mediating Variable - Dody Panca Saputra; Zainuddin, Fatlina; Rianty K. Bidin, Cici; Anisah (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of Corporate Social Responsibility (CSR) on firm value with corporate reputation as a mediating variable in banking companies listed on the Indonesia Stock Exchange. Using quantitative approach with purposive sampling, CSR measured by the Corporate Social Responsibility Disclosure Index based on GRI Standards, corporate reputation by the Corporate Image Index, and firm value by Tobin’s Q. Path analysis used to test the hypotheses. The results show that CSR has a negative and significant effect on firm value, CSR does not significantly affect corporate reputation, corporate reputation positively influences firm value, and it does not mediate the relationship between CSR and firm value.